Opazovanje sprememb v sestavi socialnih omrežij - Hlebec, Valentina (Teorija in praksa, 2007)
This paper deals with the methodological characteristics of research designs that include social time and age as interpretive variables. First we present and discuss sequential research designs and their methodological advantages and disadvantages. Second, we describe and evaluate the characteristics of the secondary studies that were used to analyze the effects of transition in Slovenia on the composition and structure of the social support networks of the elderly in Slovenia. Finally, we present characteristics of longitudinal quantitative and qualitative study, which was carried out to complement the findings of secondary studies.
Keywords: družbena omrežja; raziskovalni načrti; starost; starostniki; socialna opora; analiza omrežij